2015
DOI: 10.1111/ceo.12496
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery audit at an Australian urban teaching hospital

Abstract: This audit is the first to document modern cataract surgery, overwhelmingly dominated by phacoemulsification in an Australian population and can be used to benchmark cataract surgery outcome in an urban Australian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
6
12
0
Order By: Relevance
“…The rate of anterior vitrectomy for PCR (70%) was similar to that reported in ACS1 (75%) and in Singapore (77%), although a lower rate was reported in Australia (58%) . In the current study, all cases with vitreous loss had a PCR, but not all cases of vitreous loss are a result of PCR, and not every PCR requires an anterior vitrectomy.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The rate of anterior vitrectomy for PCR (70%) was similar to that reported in ACS1 (75%) and in Singapore (77%), although a lower rate was reported in Australia (58%) . In the current study, all cases with vitreous loss had a PCR, but not all cases of vitreous loss are a result of PCR, and not every PCR requires an anterior vitrectomy.…”
Section: Discussionsupporting
confidence: 85%
“…This prospective study provides a detailed analysis of phacoemulsification cataract surgery in a large Auckland public teaching hospital, serving approximately 25% of the New Zealand population. It illustrates improved outcomes for cataract surgery in comparison with a similar study conducted 15 years ago in Auckland (ACS1) and parallels data from other international institutions …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The rate of PCR‐VL in the current study was 3.32%. This rate is similar to previous studies from NZ and Australia but higher than rates reported in the UK and Europe . The current study population has a significantly higher mean preoperative risk of PCR‐VL (4.92%), compared with the mean preoperative risk reported in the UK study population (1.92%) .…”
Section: Prevalence Of Risk Factors For Pcr‐vl (Nz)supporting
confidence: 88%
“…In this issue, Kahawita and Goggin from South Australia add to the evidence base of cataract surgery in an Australian context . This adds to the previously published work by Australian and New Zealand centres .…”
mentioning
confidence: 87%